IV Versus Subcutaneous Enoxaparin in Critically Ill Infants and Children: Comparison of Dosing, Anticoagulation Quality, Efficacy, and Safety Outcomes*. Issue 5 (May 2017) - Diab, Yaser A.; Ramakrishnan, Karthik; Ferrell, Brandon; Chounoune, Reginald; Alfares, Fahad A.; Endicott, Kendal M.; Rooney, Sara; Corcoran, Jason; Zurakowski, David; Berger, John T.; Shankar, Venkat; Nath, Dilip S.
Abstract : Objective: Subcutaneous enoxaparin is the mainstay anticoagulant in critically ill pediatric patients although it poses several challenges in this patient population. Enoxaparin infused IV over 30 minutes represents an attractive alternative, but there is limited experience with this route of administration in children. In this study, we assess dosing, anticoagulation quality, safety, and clinical efficacy of IV enoxaparin compared to subcutaneous enoxaparin in critically ill infants and children. Design: Retrospective single-center study comparing dosing, anticoagulation quality, safety, and clinical efficacy of two different routes of enoxaparin administration (IV vs subcutaneous) in critically ill infants and children. Key outcome measures included dose needed to achieve target antifactor Xa levels, time required to achieve target antifactor Xa levels, proportion of patients achieving target anticoagulation levels on initial dosing, number of dose adjustments, duration spent in the target antifactor Xa range, anticoagulation-related bleeding complications, anticoagulation failure, and radiologic response to anticoagulation. Setting: Tertiary care pediatric hospital. Patients: All children admitted to the cardiac ICU, PICU, or neonatal ICU who were prescribed enoxaparin between January 2014 and March 2016 were studied. Interventions: One hundred ten patients were identified who had received IV or subcutaneous enoxaparin and had at least one postadministration peak antifactor Xa level documented. Measurements and Main Results: Of the 139 courses of enoxaparin administered, 96 were therapeutic dose courses (40 IV and 56 subcutaneous) and 43 were prophylactic dose courses (20 IV and 23 subcutaneous). Dosing, anticoagulation quality measurements, safety, and clinical efficacy were not significantly different between the two groups. Conclusions: Our study suggests that anticoagulation with IV enoxaparin infused over 30 minutes is a safe and an equally effective alternative to subcutaneous enoxaparin in critically ill infants and children.